Aplikasi Electronic Voting Berbasis Web Untuk Inu-Kirana Dan Putra-Putri Batik Kabupaten Kediri - Sukya, Fadelis (Jurnal Informatika dan Multimedia, 2016)
Inu-Kirana and Putra-Putri Batik Kediri an event activity held by the Kediri district government, especially the Department of Culture and Tourism aims to empower Kediri Tourism Kediri and batik conservation through tourism ambassador and the ambassador Batik Kediri. Inu-Kirana for election are held every 2 years while the Son-Daughter Batik elections are held once every year. In the selection of Inu-Kirana and Putra-Putri Batik Kediri still use some social media as a means to determine the winner of many participants, so the need for a system that can handle the problems in determining the winner. Work began with data collection information about Inu-Kirana and Putra-Putri Batik and manufacture of a series of processes of registration and the electoral process. A series of trials conducted to test the correctness of the application and suitability of the application to the needs of event organizers. In the end, the application is successfully used as a medium of registration and election Inu-Kirana and Putra Putri Batik Kediri and can be exploited further.